Current status of hand-arm vibration syndrome in China -Occurrence, laws, and measures of prevention and control - Xing, Gao; Li, Sun; Hua, He Li; Yao, Liu Yao; Fang, Wei Yun; Qi, Liu Zhao (Canadian Acoustics, 2011)
Various reports of HAV exposures in China are presented and regulations to prevent and control HAVS, and the new national prevention and control program for occupational diseases, is outlined. Studies were conducted to investigate joint damage in exposed workers and changes in x-ray images were examined. In 1982, Chang Jizeng et al. investigated a group of polishing and grinding workers. Among them, 41.2% had hand tendon contractures, while the control groups had none. In 2009, there were more than 1.5 million coal miners in China and most of them worked underground and were exposed to HAV. In October 1985, China published and implemented the national standard that has played a positive role in promoting work on prevention and control of vibration disease. More research is being done on hand numbness, pain, sensomy dysfunction, peripheral nerve injumy, and vibration perception thresholds and their clinical significance for assessing HAVS.